2013
DOI: 10.5902/1980509810545
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização da fauna edáfica em plantios de <i>Eucalyptus</i> spp.

Abstract: RESUMOSolos florestais propiciam boas condições para o desenvolvimento e estabelecimento da fauna edáfica, devido principalmente à deposição de serrapilheira. No entanto, sistemas conduzidos em monoculturas por fornecerem um único substrato alimentar, podem propiciar o desenvolvimento de determinados grupos faunísticos em detrimento de outros, ocasionando surtos de espécies-praga. O objetivo deste trabalho foi caracterizar a fauna edáfica e sua relação com as variáveis meteorológicas, em plantios de Eucalyptus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…The Coleoptera, Collembola and Hymenoptera orders showed the highest number of individuals in relation to the total population, with 15.34, 29.88 and 36.72%, respectively; all these groups together, they represented 81.94% of the total organisms (Table 1). This result corroborates to those of Garlet et al (2013) that verified in eucalyptus plantations higher proportions of organisms of the groups Coleoptera and Hymenoptera in relation to the total population.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The Coleoptera, Collembola and Hymenoptera orders showed the highest number of individuals in relation to the total population, with 15.34, 29.88 and 36.72%, respectively; all these groups together, they represented 81.94% of the total organisms (Table 1). This result corroborates to those of Garlet et al (2013) that verified in eucalyptus plantations higher proportions of organisms of the groups Coleoptera and Hymenoptera in relation to the total population.…”
Section: Resultssupporting
confidence: 92%
“…Tews et al (2004) showed that the greater diversity of groups can provide a greater amount of exploitation of the environmental resources, with the contribution of a more diversified covered with vegetation. According to Garlet et al (2013), the increase in the deposition of plant material, due to the increase in the age of forest stands, provides better conditions for the development of edaphic fauna. Almeida et al (2017), in a study with different cropping systems showed that the native forest presented the highest value for this index, stating such result is due to the diversity of vegetal material contributed to the soil.…”
Section: Areasmentioning
confidence: 99%
“…Tropical secondary forests are environments with a richness of species and micro-habitats that can be used by a variety of organisms. When these forests are replaced by monocultures, there is a simplification of the environment that reflects throughout the biota, including in the edaphic fauna community (Baretta et al, 2011;Frevolente et al, 2012;Garlet et al, 2013;Chang et al, 2017;Laird-Hopkins et al, 2017;Kooch et al, 2018). This is what happened to the non-girdled eucalyptus areas with lower values for abundance, richness and diversity when compared to the other areas analyzed.…”
Section: Discussionmentioning
confidence: 98%